A comparative study on conventionally prepared MnFe2O4 nanospheres and template-synthesized novel MnFe2O4 nano-agglomerates as the electrodes for biosensing of mercury contaminations and supercapacitor applications. (10th November 2018) - Kogularasu, Sakthivel; Akilarasan, Muthumariappan; Chen, Shen-Ming; Elaiyappillai, Elanthamilan; Johnson, Princy Merlin; Chen, Tse-Wei; Al-Hemaid, Fahad M.A.; Ali, M. Ajmal; Elshikh, Mohamed Soliman
Abstract: For the first time, Manganese ferrite (MnFe2 O4 ) with two different catalytic and morphological properties were synthesized through the conventional and template-synthetic approaches. The typical conventionally prepared MnFe2 O4 particles attained nanoscaled spherical structure, and the unique structured novel MnFe2 O4 nano-agglomerates were conquered by the template synthesis. The templates of MnCO3 made MnFe2 O4 to attain the nano-agglomeric structure with the abundant electroactive surface area and copious catalytic sites, which were confirmed through the structural, morphological, elemental, and electrochemical investigations. By the recent reports, the supercapacitor and heavy metal detection properties of MnFe2 O4 were recognized. Therefore, both the MnFe2 O4 nanospheres (NSs), and MnFe2 O4 nano-agglomerates (NAs) were applied for the detection of Hg(II) ions in real samples, and also for the supercapacitor applications. Both the materials exhibited moral parameters in electrochemical sensing and supercapacitor applications, but the results obtained for the MnFe2 O4 NAs is quite high (LOD: 0.14 nM and Specific capacitance: 1283 F/g at 5 mV/s) when compared to the NSs. Finally, the MnFe2 O4 NAs was employed to be an active participant in supercapacitor and also to detect Hg(II) ions in seafood and industrial wastewater samples. Graphical abstract: Highlights: For the first time, unique structured novel MnFe2 O4 nano-agglomerates were conquered by the template synthetic approach. The typically synthesized MnFe2 O4 nanospheres were compared with the template synthesized nano-agglomerates. As a comparison study, both the MnFe2 O4 nanospheres and nano-agglomerates were applied for the detection of Hg(II) ions, and also for the supercapacitor applications. The results obtained for the MnFe2 O4 nano-agglomerates is quite high (LOD: 0.14nM and Specific capacitance: 1283 F/g at 5 mV/s) on compared to the nanospheres.